Incidencias de las marcas verdes, sus políticas públicas y la normativa jurídica en protección medio ambiental en Canadá, Estados Unidos y México. - Aguiar Chávez, Ruth Mercedes (2023)
The purpose of this research is to identify existing public policies and legal norms in North America and determine their real impact on environmental conservation. It has a qualitative approach, for which the following types of methods have been used: exploratory, descriptive, explanatory, and deductive methods. Within the American continent, the countries that stand out the most for their resources, technology, innovation, territorial expanse, and development are Canada, the United States, and Mexico – powers that produce millions of products per day. Their public policies and legal regulations must ensure that production is carried out consciously with the planet. Given the importance of environmental conservation in North America, public policies such as Federal Laws for the control of air and water pollution, toxic substances, resource conservation, fishing laws, laws for the transportation of hazardous goods, pesticide control laws, and policies focused on the conservation and maintenance of natural resources are prominent. Similarly, North America's legal norms for green labeling emphasize laws against deceptive labeling, food and drug laws, consumer protection laws, and organic labeling standards. In Ecuador, the Organic Law of Water Resources, the Organic Environmental Code, Consumer Defense Law, and Organic Law for Rationalization, Reuse, and Reduction of Single-Use Plastics are notable. As a conclusion from this research, it is emphasized that North American public policies are directed towards environmental conservation, and legal norms are focused on ensuring that products are optimal for human consumption. For this reason, none of these laws are aimed at regulating green labels for environmental protection, highlighting that these labels ensure environmental care from raw material sourcing to the final result. 4 KEYWORDS: GREEN BRANDS/ TLCAN/ T-MEC/ PILITICAL ECOLOGY/ SUSTAINABLE DEVELOPMENT